2022
DOI: 10.53365/nrfhh/154960
|View full text |Cite
|
Sign up to set email alerts
|

Current antithrombotic therapies and prospects of natural compounds in the management of the thrombotic disorder

Abstract: Thrombosis-associated cardiovascular and cerebrovascular disorders are the leading causes of global mortality and morbidity; this rate is alarmingly rising. A diverse class of antithrombotic drugs like antiplatelet and anticoagulant agents are frequently used to manage thrombus-induced physiological consequences, including cardiovascular and cerebrovascular diseases. But these agents have reported producing a series of adverse effects on the body, including potential bleeding episodes, which makes it urgent to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 213 publications
(124 reference statements)
0
1
0
Order By: Relevance
“…When compared to standard, the methanolic extract of IHSE showed a dosedependent reduction in paralysis and death times (Figure 3). Numerous investigations have shown that alkaloids, phenolic, flavonoid, and tannin compounds are what give plants their anthelmintic effects (Athanasiadou et al, 2001;Aziz et al, 2014;Mazumder et al, 2023). By attaching to free host animal proteins or glycoprotein on the parasite's cuticle in the gastrointestinal tract (GIT), tannins may cause death (Marzan et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…When compared to standard, the methanolic extract of IHSE showed a dosedependent reduction in paralysis and death times (Figure 3). Numerous investigations have shown that alkaloids, phenolic, flavonoid, and tannin compounds are what give plants their anthelmintic effects (Athanasiadou et al, 2001;Aziz et al, 2014;Mazumder et al, 2023). By attaching to free host animal proteins or glycoprotein on the parasite's cuticle in the gastrointestinal tract (GIT), tannins may cause death (Marzan et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…These issues can impact the safety and efficacy of thrombin inhibitors and require careful management and individualization of treatment. Therefore, discovering novel thrombin inhibitors from herbal medicine may be a promising option, offering natural compounds with potent and selective antithrombin activity and fewer side effects 26 , 27 .…”
Section: Introductionmentioning
confidence: 99%